2018
DOI: 10.1210/en.2018-00115
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Role of Estrogen-Related Receptor α in Lipid- and Fasting-Induced Hepatic Steatosis in Mice

Abstract: Given the increasing prevalence of obesity and the metabolic syndrome, identification of intrinsic molecular programs responsible for ensuring fuel homeostasis and preventing metabolic disease is needed. We investigated whether the orphan nuclear receptor estrogen-related receptor α (ERRα), a major regulator of energy metabolism, plays a role in lipid homeostasis and the development of nonalcoholic fatty liver disease (NAFLD) in response to chronic high-fat diet (HFD) consumption and long-term fasting. Systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 30 publications
2
41
1
Order By: Relevance
“…All three of these aspects are believed to contribute to NAFLD with the contribution of each of these aspects varying under different physiological conditions. However, global ERRα knockout mice did not display NAFLD compared to our ERRαLKO mice 43 , 53 , 54 . This discrepancy is likely due to reduced nutrient absorption in global ERRα knockout mice.…”
Section: Discussioncontrasting
confidence: 69%
“…All three of these aspects are believed to contribute to NAFLD with the contribution of each of these aspects varying under different physiological conditions. However, global ERRα knockout mice did not display NAFLD compared to our ERRαLKO mice 43 , 53 , 54 . This discrepancy is likely due to reduced nutrient absorption in global ERRα knockout mice.…”
Section: Discussioncontrasting
confidence: 69%
“…Chaveroux et al showed that the genetic and pharmacological inhibition of ESRRA activity exacerbated hepatosteatosis in rapamycin-treated mice [61]. In contrast, B'Chir et al showed that the genetic ablation of ESRRA protected against fatty liver induced in DIO [93]. Consistent with the findings in ESRRA null mice, ESRRA inverse agonists, compound 29 (C29) and compound 50 (C50), also show obesity resistance in DIO mouse models [94][95][96].…”
Section: Esrra As a Target For Nafldmentioning
confidence: 90%
“…Moreover, the molecular clock serves as another input signal modulating ERRα levels in a circadian manner in tissues including liver and WAT (8487). Furthermore, ERRα adapts to nutritional challenges such as increased intake of a lipid-rich diet or cycles of nutrient deprivation and availability by modulating metabolic gene and metabolite levels (88, 89). Rapamycin treatment, which is known to mimic amino-acid-like starvation, as well as glucose and amino acids deprivation also affect ERRα protein stability and transcriptional networks (23).…”
Section: Role Of Errα In Adaptation To Energy Demands and Environmentmentioning
confidence: 99%
“…Genetic or pharmacological manipulation of ERRα in rodent and cell-based studies have further characterized the genes and biological programs regulated by ERRα, establishing a major role of ERRα in liver homeostasis. A list of currently known genes found either activated or repressed by ERRα in hepatocytes in a context-specific manner with evidence for direct binding of ERRα within ± 20 kb of the TSS from ChIP-based studies is summarized in Table S1 (22, 23, 82, 84, 88, 90, 95103). A schematic of these direct ERRα-regulated genes associated to general biological processes are shown in Figure 2.…”
Section: Errα Gene Network In the Livermentioning
confidence: 99%